Research on Artificial Intelligence in Human Resource Management: Trends and Prospects (Global Journal of Management and Business Research, 2023)
Applying Artificial Intelligence AI technologies in Human Resource Management HRM contributes to more capability diverse insights and analytical support to enhance people management This study presents an integrated overview of the research trends through a PRISMA-compliant bibliometric review We have analysed a dataset of 247 Scopus-indexed publications between the earliest available date 1993 till 2020 to understand the key themes and the related research focus The study shows that most research has been conducted in recent years with 70 of relevant papers published since 2010 The key themes subscribed to the development of this literature have been called out The outcome of term co-occurrence analysis highlights majority research related to AI in HRM focuses on resource allocation talent acquisition and training and development The research spotlights significant areas attributed to AI in HR functions that warrant additional research Deliberation of research gaps and recommendations on future direction is also provided
Keywords: artificial intelligence; AI; HRM; human resource management; bibliometric analysis